Análisis a resistencia a la insulina como incrementador a la glucosa sanguínea en pacientes con sobre peso con el método quimioluminiscencia en Pasaje. - Orellana Ortiz, Cruz Lisseth (2015)
The insulin resistance is characterized by one diminished capacity of insulin to perform normal physiological functions. Usually precedes clearly pathological situations such as type 2 diabetes mellitus or metabolic syndrome and is associated with conditions such as overweight or obese. Also of note other circumstances such as age, pregnancy and polycystic ovary where the insulin resistance plays an important role initially, insulin resistance generates compensatory mechanisms, such that during a period of time, the hypersecretion of insulin keep blood sugar under control.